SCALING ONLINE EDUCATION: INCREASING ACCESS TO HIGHER EDUCATION - Jacqueline F. Moloney; Burks Oakley (Online Learning, 2019)
This paper reviews online enrollment trends in higher education, describes the characteristics of online programs that have scaled successfully to meet increasing demand, identifies challenges impacting the continued growth of online enrollments in this sector, and outlines the opportunities for increasing access to higher education through scaling of online initiatives.